Differential activation of monocytes and PMNs in orofacial granulomatosis patients induced by bacterial and non-bacterial stimuli - Palestra, Francesco; Modestino, Luca; Ventrici, Annagioia; Monteforte, Arianna; Memoli, Gina; Ferrara, Anne Lise; Cristinziano, Leonardo; Poto, Remo; Rossi, Francesca Wanda; Varricchi, Gilda; De Paulis, Amato; Marone, Gianni; et al. (Frontiers in Immunology, 2025)
IntroductionOrofacial Granulomatosis (OFG) is a rare chronic inflammatory disorder characterized by persistent or recurrent swelling of the lips and oral mucosa, often accompanied by granulomatous inflammation in the orofacial region with limited effective treatment options available. Emerging evidence suggests an immune dysregulation in the development and progression of OFG. Immune cells, including monocytes and neutrophils (PMNs), are involved in autoimmune and inflammatory diseases by releasing pro-inflammatory and immunomodulatory molecules.MethodsConsidering that microbial agents have been suggested as potential triggers for OFG, in this study we evaluated the effect of LPS, fMLP and PMA on the activation of monocytes and PMNs purified by 11 OFG patients and 11 sex-and age-matched healthy donors (HDs).ResultsUpon stimulation, OFG-derived monocytes displayed a higher release of pro-inflammatory cytokines (CXCL8/IL-8, IL-6, TNF-α, IL-33) compared to HDs. Conversely, OFG-derived monocytes showed a lower release of IL-10, IFN-γ compared to HDs. Upon stimulation, peripheral PMNs from OFG patients released large amounts of TNF-α and MPO compared to HDs. In addition, OFG-derived PMNs showed high percentages of activated PMNs (CD62L-) and increased ROS production compared to HDs. Compared to HDs, OFG patients presented higher serum levels of MMP-9, MPO and TNF-α, together with MPO-DNA complexes and citrullinated histone H3 (CitH3) (two biomarkers for neutrophil extracellular traps).DiscussionThese preliminary data suggest that in presence of various stimuli, monocytes and PMNs of OFG patients displayed an activated phenotype compared to HDs. Unraveling the interplay between bacterial triggers and immune cell function in OFG will be necessary to elucidate mechanisms driving this complex disease and identify novel therapeutic targets for improved management of OFG patients.